Analisis Kewirausahaan Muslim Terhadap Keberhasilan Usaha - Mochammad Erwin Radityo; Jasmalinda Jasmalinda (ITB AAS Indonesia Surakarta, 2023)
The main problem of this research is how to analyze the relationship between the level of knowledge of Muslim entrepreneurs and the success of a business (a case study of Muslim entrepreneurs in Benteng District, Selayar Islands Regency) The main problem is raised into several sub-problems or research questions, namely: how is the relationship between the level of knowledge of Muslim entrepreneurs and the success of a business. This type of research is classified as quantitative research is a research method that is inductive, objective, and scientific in which the data obtained is in the form of numbers (score, value) or statements that are scored, and analyzed by statistical analysis. The source of data for this research is the Muslim community who work as entrepreneurs. The data collection methods used are interviews and questionnaires. Data management and analysis techniques are carried out by validity test, reliability test, simple regression analysis, correlation coefficient, determination coefficient test (R2), and t-test (partial). The results of this study indicate that: the correlation coefficient is 0.561 this value can be interpreted based on the correlation coefficient guidelines, that the relationship between the two research variables is in the category of moderately correlated relationships. And the coefficient of determination (R2) of 0.35.9 which means that the explanation of variable X to variable Y is 35.9% and the rest is explained by other variables not examined by researchers. Although the correlation coefficient test states that the level of correlation is sufficient, the partial t-test still shows that the t-count value is 3.570 and the t-table value is 1.991, which means t-count > t-table with a significance value of 0.001